CSA-based Portland-free binders to manufacture sustainable concretes for jointless slabs on ground. (30th October 2018) - Coppola, L.; Coffetti, D.; Crotti, E.; Pastore, T.
Highlights: CSA cement and SCMs were employed to develop concretes for jointless slabs on ground. OPC-free concretes have mechanical strength close to that shown by traditional concretes. Properties of CSA-based concretes is strongly influenced by curing conditions. Abstract: The paper is aimed to the evaluation of the influence of water/binder ratio, tartaric acid dosage and curing condition on rheological, elastic and physical properties of sustainable shrinkage-compensating concretes manufactured with calcium sulphoaluminate cement (CSA), anhydrite ( C S ¯ ) and supplementary cementitious materials (SCMs)/lime (CH) compound in place of ordinary Portland cement (OPC). Results indicated that tartaric acid-based set-retarding admixture governs the behavior of concrete both in fresh and hardened state. In addition, according to Abram's model, results evidenced the water/binder ratio as a key factor in strength gain. Moreover, tartaric acid allows the production of shrinkage-compensating Portland-free concretes particularly indicated for slabs on ground. Finally, by replacing OPC with SCMs and lime, it is possible to obtain, both for CO2 -emissions and energy consumption, a reduction up to 60% at equal strength class respect to an OPC-based concrete.